Assessing the Adoption of Circular Economy among Women-Led MSMEs in Metro Manila: A Pilot Study - Jovito Jose P. Katigbak; Jemimah Joanne C. Villaruel (Philippine Institute for Development Studies (PIDS), 2023)
Buoyed by favorable developments at the global and regional levels, circular economy (CE) has been emerging in the Philippines due to an increasing call for the effective mainstreaming of sustainable principles and practices across various economic sectors. Often characterized as an industrial system that is regenerative or regenerative by design, CE presents guidelines that enable business-, society-, and environment-friendly economic development. This is vital for the Philippines as it seeks to address waste management issues and reduce carbon emissions through the advancement of Sustainable Development Goal 12: Sustainable Consumption and Production. Notably, the government has enacted and implemented several laws, policies, and regulations to steer the country towards cleaner production. The private sector and external partners are similarly promoting CE through their respective programs, projects, and activities. Notwithstanding the current initiatives, there is a need to focus national thrust and efforts towards the micro, small, and medium enterprises (MSMEs) as they comprise over 99 percent of all businesses in the Philippines. This is especially true for women-led MSMEs as they composed around 60 percent of business name registrations in 2019. Hence, this pilot study sought to assess the level of CE adoption among WMSMEs in Metro Manila through a survey questionnaire, which garnered 58 responses. It found that there is a low level of awareness regarding CE principles and CE-related government programs among the respondents and lack of demand for circular goods/services by the customers. These translate to misalignment between CE principles and their firm's strategy and business model. The results also show that majority of the WMSMEs in Metro Manila still practice linear methods as evidenced by non-use of renewable resources, lack of resource recovery strategies and post-sales services, and absence of ecodesign. The respondents exhibited somewhat positive performance in waste management. In addition, WMSMEs do not engage in CE-oriented partnerships and collaborations with their co-enterprises and customers. Accordingly, the Philippine government may consider a multi-level approach in mainstreaming CE among (W)MSMEs. Micro level initiatives may include advocacies on CE, training programs for MSMEs, provision of incentives and business support schemes. At the meso level, smart regulation and mini eco-parks may be explored. Lastly, the development of a national framework and monitoring mechanism may be critical undertakings at the macro level.
Keywords: 330; circular economy; Philippine Development; Sustainable Development Goals; SMEs; women-led MSMEs